2011
DOI: 10.1179/14653121141308
|View full text |Cite
|
Sign up to set email alerts
|

Banding versus bonding of first permanent molars: a multi-centre randomized controlled trial

Abstract: This study shows that as part of fixed appliance therapy, American Orthodontics photoetched first permanent molar bands cemented with 3M ESPE Ketac-Cem perform better than American Orthodontics low profile photo-etched and mesh-based first permanent molar tubes bonded with 3M Unitek Transbond XT in terms of failure behaviour and molar enamel demineralization.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
18
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 23 publications
(19 citation statements)
references
References 30 publications
1
18
0
Order By: Relevance
“…In one of the research studies, the survival analysis demonstrated molar bonds were more likely to fail compared with molar bands [2].…”
Section: Discussionmentioning
confidence: 99%
“…In one of the research studies, the survival analysis demonstrated molar bonds were more likely to fail compared with molar bands [2].…”
Section: Discussionmentioning
confidence: 99%
“…2,3,[9][10][11] Banding is associated with gingival enlargement and increased pocket depth. 4,8,[12][13][14][15] The adolescents have more gingival enlargement than the adults.…”
Section: Discussionmentioning
confidence: 99%
“…However there is a high risk of bonding failure and white spot lesion associated with molar tubes. [2][3][4] In a very recent Cochrane review on banding versus bonding, it has been found that there is statistically significant difference on the rate of banding versus bonding failures. According to that review there is 57 % risk of attachment failure in case of bonded tubes whereas the risk is only 25 % in case Dr Dashrath Kafle, 1 Dr Aradhana Agarwal, 2 Dr Sita Shrestha, 3 Dr Biplov Adhikari of banded attachments.…”
Section: Introductionmentioning
confidence: 99%
“…1 Decalcification of the dental enamel is lower with bands than with tubes bonded with a light curing system. 1,2 However, patient hygiene may be compromised, allowing for plaque accumulation and for the development of periodontal problems, which are more critical in Declaration of Interests: The authors certify that they have no commercial or associative interest that represents a conflict of interest in connection with the manuscript. adult patients.…”
Section: Introductionmentioning
confidence: 99%
“…Despite the advantages in terms of comfort, minor periodontal damage 3 and shorter chair time, direct bonding of molars is not yet universally accepted among orthodontists. Randomized clinical trials 2,6 validated by a systematic review 7 have shown that failure of tubes bonded to molars is considerably higher than molars banded with glass ionomer cement. However, the vast majority of patients in these studies consisted of children and adolescents.…”
Section: Introductionmentioning
confidence: 99%